Ab Initio Molecular Dynamics Study of Hydrogen Cleavage by a Lewis Base [tBu3P] and a Lewis Acid [B(C6F5)3] at the Mesoscopic Level—Dynamics in the Solute–Solvent Molecular Clusters. Issue 17 (26th August 2014) - Pu, Maoping; Privalov, Timofei
Abstract With the help of state‐of‐the‐art ab initio molecular dynamics methods, we investigated the reaction pathway of the tBu3P + H2 + B(C6F5)3 system at the mesoscopic level. It is shown that: i) the onset of H2 activation is at much larger boron⋅⋅⋅phosphorus distances than previously thought; ii) the system evolves to the product in a roaming‐like fashion because of quasi‐periodic nuclear motion along the asymmetric normal mode of P⋅⋅⋅HH⋅⋅⋅B fragment; iii) transient configurations of a certain type are present despite structural interference from the solvent; iv) transient‐state configurations with sub‐picosecond lifetime have potentially interesting infrared activity in the organic solvent (toluene) as well as in the gas phase. The presented results should be helpful for future experimental and theoretical studies of frustrated Lewis pair (FLP) activity.